Bio-orthogonally activated tetraphenylene-tetrazine aggregation-induced emission fluorogenic probes. Issue 42 (18th October 2022) - Teng, Yu; Zhang, Rongrong; Yang, Bingbing; Yang, Hong; Li, Xiang; Yin, Dali; Feng, Xinchi; Tian, Yulin
Abstract : Tetraphenylene-tetrazine derivatives were developed as bio-orthogonally activated aggregation-induced emission (AIE)-type fluorogenic probes for live-cell imaging. Abstract : Tetrazine-based bio-orthogonally activated fluorogenic probes have drawn great attention due to their excellent performance in bioimaging; however, most of them suffer from aggregation-caused quenching (ACQ) problems. Herein, we developed a set of novel tetrazine-modified tetraphenylenes (TPEs) as bio-orthogonally activated aggregation-induced emission (AIE) fluorogenic probes. Both the fluorescence and AIE features are quenched by tetrazine, which is mediated by the through-bond energy-transfer (TBET) mechanism, and are activated upon converting tetrazine to pyridazine via the inverse electron-demand Diels–Alder (iEDDA) reaction. The activated cycloadducts displayed a notable fluorescence enhancement, a large Stokes shift, a high fluorescence quantum yield, and evident AIE-active features. Manipulating the length and position of the π-linker enables fine-tuning of the photophysical properties of the probes, while an overlong planar π-linker leads to AIE-to-ACQ transformation. We also designed bi-tetrazyl-substituted probes, which exhibited a higher turn-on ratio than the mono-tetrazyl analogs owing to the 'double-quenched' function. When they reacted with double-clickable linkers, fluorescent macrocycles were obtained because of the restriction of the free rotation of the phenyl rings of TPE. Using an organelle-pretargeting strategy, we succeeded in applying these probes for mitochondria-specific bio-orthogonal imaging in live cells under no-wash conditions, which is expected to provide a powerful tool for biomedical applications.